Duration of the legislative approvals of international agreements: Evidence from Mercosur - Araujo, André Leite [UNESP] (FapUNIFESP (SciELO), 2024)
Why do some agreements take longer to be approved by national legislatures than others? This question motivates this research, which aims to understand how the nature of coalitions influences the time for the approval of international agreements. To this end, the analysis covers all agreements signed within Mercosur between 1995 and 2019 and the internalisation processes in four member states. This study provides insights into which variables define motivation when voting regionalism bills, concluding that the government-opposition cleavage drives the parliamentarians’ behaviour on this topic, with the size of the president’s party being the decisive factor in parliamentary procedures.
Keywords: Coalitions; Foreign Policy Analysis; Mercosur; Parliaments; Regionalism; Treaties